Smart and Healthy Generation: Sexuality Education and Health Check-Up with Garuda Parang Catholic Junior High School Students in Magetan - Kolektus Oky Ristanto; Cicilia Deandra Maya Putri; Audrey Gabriella Titaley; Maria Mediatrix Andita Garindra Putri (Amirul Bangun Bangsa, 2026)
The community service program